Novel insight into the microstructure evolution and defect formation of nano-polycrystalline CoCrFeNi HEA during vacuum hot-pressing sintering - Bowen Dong; Liwei Chen; Zhenpeng Wu; Jinchuan Jie (Journal of Materials Research and Technology)
The concept of nano-polycrystalline (NC) HEAs is proposed to overcome the performance bottleneck of CoCrFeNi HEAs, which are characterized by high ductility but relatively low strength. In this study, a CoCrFeNi HEA was initially prepared by arc melting to achieve a compositionally homogeneous alloy. Molecular dynamics (MD) simulations were then conducted to investigate the microstructure evolution and mechanical performance of CoCrFeNi HEAs under conditions relevant to vacuum hot-pressing sintering (VHPS). The results reveal that CoCrFeNi nanoparticles connect through the interdiffusion of atoms around the interface, eventually forming grain boundaries upon solidification. The grain growth process of NC HEAs is revealed in situ. Larger nanoparticle sizes are shown to promote the formation of inherent cracks due to the limited flowability of the alloy melt, which significantly deteriorates mechanical properties by accelerating fracture before the matrix reaches its critical stress. The simulation results align well with experimental observations and demonstrate the feasibility of applying this model to large-scale NC HEA production with sufficient computational resources.